2015
DOI: 10.22260/isarc2015/0088
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a Three-Axis Inclinometer to the Automated Blade Control System of Excavator

Abstract: -Partly automated blade control of excavator has been studied. Main focus of the study were to find means to control one of the excavator's work cylinders automatically while machine operator controls the rest of non-automated work cylinders.This article concentrates on the suitability of a certain inclinometer sensor for partly automated blade control of excavator. Test device was built where inclinometers output data controlled hydraulic cylinder and the statical and dynamical properties of the cylinder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The impedance control was also discussed later in [37] for a tele-operated excavator. Recently, partial automated blade control has been studied in [38] to control one of the excavator's work cylinders while the machine operator controls the rest of non-automated work cylinders. A time-delay control with switching action (TDCSA) using an integral sliding surface was proposed for the control of a 21-tonne robotic excavator [39], whereby analysis and experiments showed that using an integral sliding surface for the switching action of TDCSA was better than using a PD-type sliding surface.…”
Section: Autonomous Excavationmentioning
confidence: 99%
“…The impedance control was also discussed later in [37] for a tele-operated excavator. Recently, partial automated blade control has been studied in [38] to control one of the excavator's work cylinders while the machine operator controls the rest of non-automated work cylinders. A time-delay control with switching action (TDCSA) using an integral sliding surface was proposed for the control of a 21-tonne robotic excavator [39], whereby analysis and experiments showed that using an integral sliding surface for the switching action of TDCSA was better than using a PD-type sliding surface.…”
Section: Autonomous Excavationmentioning
confidence: 99%
“…Mohammed and Athraa 8 examined nonlinear modelling of a fuzzy control design for a 4-DOF (degree of freedom) robotic backhoe excavator. Furthermore, Immonen et al 9 studied the applicability of a threeaxis tiltmeter in an automatic control system of an excavator. Mohammad Shahidul Hasan 10 investigated modelling and issues with the remote control of an industry excavator.…”
Section: Introductionmentioning
confidence: 99%